Epidemiological Profile and Risk Factors for Retinopathy in Moroccan Type 2 Diabetics - GUERBOUB, Ahmed anas; HALOUACHE, Ali; MOUZARIA, Yassine; ISOUANI, Jade; ERRAHALI, yassine (International Journal of Innovative Research in Medical Science, 2024)
Objective: To evaluate the ophthalmic impact, compare characteristics, and identify risk factors related to diabetic retinopathy (DR) in patients seen for the first time in consultation. Patients and methods: This descriptive cross-sectional study was conducted during the period from June to December 2018, of a representative sample of 156 diabetics recruited in the department of endocrinology diabetology and metabolic diseases of the Military Hospital of Instruction Mohamed V of Rabat. Results: Among the 156 patients included in our study, 86 (55.1%) had a normal eye fundus, while 70 (44.8%) had DR. Glycemic control, age of diabetes, as well as diabetic nephropathy and abdominal obesity were risk factors (OR>1, p<0.05), while physical activity and development of lean body mass are protective factors (OR<1, p>0.05) of diabetic retinopathy. Conclusion: Our study reflects the epidemiological profile of the Moroccan population, where the prevalence of DR remains high, with poor control of risk factors.